On the position of dative DPs in Spanish middle-passive sentences - Imanol Suárez-Palma (Isogloss)
This paper examines external possession between a dative possessor and a relational noun in Spanish middle-passive configurations. The dative DP in these contexts must surface preverbally in out-of-the-blue contexts, either by itself –presumably in preverbal subject position–, or along with the theme containing the possessee. When the dative precedes the theme, it cannot be assumed that the former is left-dislocated while the latter sits in preverbal subject position, for this would imply a violation of locality under a low applicative analysis of dative possessors: Tº would skip the possessor argument in Spec,ApplP to probe the possessee in Applº’s complement position to its specifier. Rather, I provide data showing that preverbal DPs –dative or otherwise– in Spanish middle-passive contexts are clitic left-dislocations co-referring with empty pronouns in argument position. I offer a biclausal analysis of these configurations that avoids any potential intervention effects, while at the same time accounting for the extra-sentential properties of these constituents.